PAH growth assisted by five-membered ring: pyrene formation from acenaphthylene - Raj, Abhijeet (Combustion theory and modelling, 2022)
To investigate the role of five-membered rings in the growth of polycyclic aromatic hydrocarbons (PAHs) in flames, the conversion of acenaphthylene to pyrene with substituted phenalene as intermediate is studied through quantum calculations using CBS-QB3 composite method. Two pathways are considered, where one initiates with H-abstraction from the five membered ring on acenaphthylene, while the other initiates with H-addition on it. Both the pathways are then followed by subsequent C 2 H 2 addition reactions on the radical sites. With the first C 2 H 2 addition, a substituted phenalene-type species is formed, which undergoes another C 2 H 2 addition reaction to lead to pyrene formation. The reaction kinetics are calculated using transition state theory, and the new reactions are added to a detailed hydrocarbon mechanism to test their effect on the profiles of pyrene and other PAHs. Among the H-abstraction-C 2 H 2 -addition (HACA)-type mechanisms for pyrene formation, the proposed reactions have a minor contribution in pyrene formation as they mainly form 1-ethynyl-acenaphthylene and phenanthrene. Through mechanism analysis, the reactions primarily responsible for pyrene formation are highlighted that require further investigation.